2014
DOI: 10.2355/isijinternational.54.1715
|View full text |Cite
|
Sign up to set email alerts
|

Back Stress Work Hardening Confirmed by Bauschinger Effect in a TRIP Steel Using Bending Tests

Abstract: Martensite formed in TRIP steels causes large work hardening. The expectation that this is due to the back stresses induced into the ferrite by the hard martensite was examined by the Bauschinger effect after room temperature tensile straining of a TRIP steel into which the martensite had been introduced by prior straining at -50°C. Bending tests were employed to detect the Bauschinger effect. The tests showed that the compressive flow stress became much smaller than the tensile flow stress and confirmed the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Acquisition of the images was performed in situ to eliminate the possibility of transformation or plasticity owing to back-stresses [46], which builds up during the unloading stage. It is worth noting here, that in preliminary studies of this material, higher fractions of transformation product were observed in samples that had undergone unloading cycles compared to those strained directly to the same final macro strain.…”
Section: Discussionmentioning
confidence: 99%
“…Acquisition of the images was performed in situ to eliminate the possibility of transformation or plasticity owing to back-stresses [46], which builds up during the unloading stage. It is worth noting here, that in preliminary studies of this material, higher fractions of transformation product were observed in samples that had undergone unloading cycles compared to those strained directly to the same final macro strain.…”
Section: Discussionmentioning
confidence: 99%
“…The back stress concept was later used by many groups to explain the strengthening of a metal matrix by secondphase particles in the 1970s [44][45][46]. More recently, back stress has been used to explain the hardening behavior and Bauschinger effect in TRIP steels [47], the transient plastic flow during creep [48], the Bauschinger effect in thin films [38], the hysteresis loop under cyclic loading [49], the extra strain hardening of HS materials [1,2,27,50,51], etc. These reports show that the back stress concept has been widely, if not fully, accepted by the materials community.…”
Section: Brief History Of Back Stressmentioning
confidence: 99%
“…Some examples of the method used for steels and nonferrous metals are given in reference [7]. The method has been successfully applied to thin sheets of transformation-induced plasticity (TRIP) steel of 1.2 mm thickness [8]. In this work, the method is used to examine the Bauschinger effect in thin plates of IF steels.…”
Section: Introductionmentioning
confidence: 99%
“…The Bauschinger effect is understood in such a manner that dislocations move under the external stress which is balanced with the friction force and the internal force (the back stress) [2,3,8]. The friction force action is symmetrical with regard to the forward and reverse flow, while the back stress is asymmetrical.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation